2014
DOI: 10.1074/jbc.m114.581363
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Zinc on Particulate Methane Monooxygenase Activity and Structure

Abstract: Background: Particulate methane monooxygenase (pMMO) is a membrane-bound metalloenzyme that oxidizes methane to methanol. Results: Metal binding data and crystal structures reveal that zinc inhibits pMMO at two sites. Conclusion: Zinc does not inhibit pMMO by binding at the active site but may hinder another function such as proton transfer. Significance: New insight into the function of an environmentally and industrially important enzyme has been obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
173
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 67 publications
(185 citation statements)
references
References 63 publications
9
173
1
2
Order By: Relevance
“…There are conflicting data regarding whether or not CuMbn addition affects the activity of purified pMMO (47, 54). Apo Mbn addition has been reported to increase activity (54), but surplus copper or zinc binding can inactivate pMMO (55, 56), and it may be that apo Mbn is merely removing inhibitory metals.…”
Section: Methanobactinsmentioning
confidence: 99%
“…There are conflicting data regarding whether or not CuMbn addition affects the activity of purified pMMO (47, 54). Apo Mbn addition has been reported to increase activity (54), but surplus copper or zinc binding can inactivate pMMO (55, 56), and it may be that apo Mbn is merely removing inhibitory metals.…”
Section: Methanobactinsmentioning
confidence: 99%
“…50,96 Moreover, zinc inhibits pMMO, likely by binding in the crystallographic site, leading to the hypothesis that the coordinating residues, which are conserved, could be involved in proton transfer. 97 It is unclear if copper binding at this site is functionally important. Samples of pMMOs in which copper is observed in the PmoC site have been prepared in the presence of extra copper, while pMMOs that have not been treated with additional copper require zinc to crystallize.…”
Section: Aerobic Methane Oxidationmentioning
confidence: 99%
“…Three additional crystal structures of pMMO have been published, showing only asingle Cu ion in site A. [10] Unfortunately,t he crystal structures did not settle the location and composition of the pMMO active site.Computational studies have supported site Aa nd have indicated that both mono-and dinuclear Cu sites are reactive enough to oxidise CH 4 . [3,11] On the other hand, Chan and co-workers have argued that the active site instead consists of three Cu ions,not observed in the crystal structure,but coordinated by residues from PmoA and PmoC.…”
mentioning
confidence: 99%